2005
DOI: 10.1007/s00213-005-0156-7
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence for medication effects on functional abnormalities in the amygdala and anterior cingulate in bipolar disorder

Abstract: Rationale: Abnormal amygdala and frontocortical responses to emotional stimuli are implicated in bipolar disorder (BD) and have been proposed as potential treatment targets. Objectives: The aim of this study was to investigate amygdala and frontocortical responses to emotional face stimuli in BD and the influences of mood-stabilizing medications on these responses. Methods: Functional magnetic resonance imaging was performed while 17 BD participants (5 unmedicated) and 17 healthy comparison (HC) participants v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
135
5
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(163 citation statements)
references
References 25 publications
21
135
5
2
Order By: Relevance
“…BD seem to involve a hyperactivated right fronto-parietal network particularly implicated in emotion perception (e.g., Blumberg et al, 2005;Wessa et al, 2007;Robinson et al, 2008;Pavuluri et al, 2009;Chen et al, 2010;Lee et al, 2010;Morris et al, 2012;Liu et al, 2012), but also supported by the right (fronto) parietal dysfunction shown by the visual field, dichotic listening and positron emission tomography studies mentioned above (Bruder et al, 1981(Bruder et al, , 1989(Bruder et al, , 1992(Bruder et al, , 1994Berns et al, 2002). Based on these findings, we hypothesis that a right hemisphere dysfunction should particularly affect the left hand bisection bias in BD patients compared to healthy controls.…”
Section: Introductionmentioning
confidence: 70%
“…BD seem to involve a hyperactivated right fronto-parietal network particularly implicated in emotion perception (e.g., Blumberg et al, 2005;Wessa et al, 2007;Robinson et al, 2008;Pavuluri et al, 2009;Chen et al, 2010;Lee et al, 2010;Morris et al, 2012;Liu et al, 2012), but also supported by the right (fronto) parietal dysfunction shown by the visual field, dichotic listening and positron emission tomography studies mentioned above (Bruder et al, 1981(Bruder et al, , 1989(Bruder et al, , 1992(Bruder et al, , 1994Berns et al, 2002). Based on these findings, we hypothesis that a right hemisphere dysfunction should particularly affect the left hand bisection bias in BD patients compared to healthy controls.…”
Section: Introductionmentioning
confidence: 70%
“…In adults with BD, one study found that, compared with unmedicated patients, medicated patients had increased dorsolateral prefontal cortex and anterior cingulate activation during a Stroop task (51). In contrast, two studies of medicated and unmedicated bipolar adults (52,53) and one study in children with BD (54) found more marked differences in activation between unmedicated patients and controls than between medicated patients and controls, suggesting that medication may lead to type II, rather than type I, errors. Data in adults with BD (37) or depression (55) also suggest that lithium, antipsychotics, and antidepressants may normalize neural activation in response to facial expressions.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, only 25% of patients were currently taking lithium, while a slight majority (39%) were unmedicated. While very little is currently known regarding the functional significance of lithiumassociated brain changes, functional neuroimaging studies offer preliminary evidence that mood-stabilizing medications may normalize functional abnormalities within frontotemporal neural systems in bipolar illness (Blumberg et al 2005). In addition, two recent functional neuroimaging studies have reported decreases in task-associated physiological activity following 2 weeks of lithium treatment in both euthymic bipolar patients ) and healthy volunteers .…”
Section: Discussionmentioning
confidence: 99%